Effect of Misalignment between Hospital and Provincial Formularies on Medication Discrepancies at Discharge: PPITS (Proton Pump Inhibitor Therapeutic Substitution) Study - Chua, Doson (Canadian Society of Hospital Pharmacists, 2012)
BACKGROUND: Medication discrepancies may occur on admission, transfer, or discharge from hospital. Therapeutic interchange within a drug class is a common practice in hospitals, and orders for specific proton pump inhibitors (PPIs) are often substituted with the hospital’s formulary PPI through therapeutic interchange protocols. Rabeprazole is the PPI on the formulary of the British Columbia PharmaCare program. However, different PPIs may appear on the formularies of the province’s hospitals. This misalignment and use of therapeutic interchange may lead to increased rates of medication discrepancies at the time of discharge. OBJECTIVE: To evaluate the effect of formulary misalignment for PPIs between St Paul’s Hospital in Vancouver and the British Columbia PharmaCare program and use of therapeutic interchange on the occurrence of medication discrepancies at discharge. METHODS: A cohort chart review was performed to compare discharge discrepancy rates for PPI orders between 2 periods: June 2006 to June 2008, when the same PPI appeared on the hospital and provincial formularies, and July 2008 to July 2010, when the designated PPIs differed between the hospital and provincial formularies. Data for the first study period were used to establish the baseline discharge discrepancy rate, and data for the later period represented the discharge discrepancy rate in the presence of misalignment between the hospital and PharmaCare formularies. RESULTS: The discharge discrepancy rate for PPIs was 27.3% (24/88) when the 2 formularies were aligned and 49.1% (81/165) when the formularies were misaligned. This represents an absolute increase of 21.8 percentage points in the risk of discharge discrepancies (95% confidence interval 9.8–33.9 percentage points; p < 0.001) when the hospital and provincial formularies were misaligned and the hospital’s therapeutic interchange protocol was used. CONCLUSIONS: Misalignment between the PPIs specified in the hospital and provincial formularies, combined with use of therapeutic interchange, was associated with a significant increase in medication discrepancies at discharge.